Determinants of male involvement in antenatal care at Palabek Refugee Settlement, Lamwo district, Northern Uganda - Irene Auma; Dinah Nabaweesi; Sam Orech; John Bosco Alege; Allan Komakech (BMC, 2023)
Abstract Background In 2014, Uganda launched the National Male Involvement Strategy in Maternal and Child Health. In 2020, the District Health Management Information System report for Lamwo district, where Palabek Refugee Settlement is located, indicated a 10% male involvement in antenatal care (ANC) at the settlement. We investigated determinants of male involvement in ANC in Palabek Refugee Settlement to inform programs on improvement of male involvement in ANC in a refugee setting. Methodology We conducted a community-based cross-sectional analytical study among a proportionate sample of mothers in Palabek Refugee Settlement from October-December 2021. Using a standardized questionnaire, we collected information on demographics and the constructs of the socio-ecological model where consent was given. We summarized data in tables and figures. We used Pearson chi-square test to determine significance of independent variables at bivariate level. A multivariable logistic regression model was run for all variables found significant at bivariate analysis to determine association between the different independent variables and male involvement in ANC. Results We interviewed 423 mothers. The mean age of their male partners was 31 years, SD 7. 81% (343/423) of male partners had formal education, with 13% (55/423) having a source of income and 61% (257/423) having access to ANC information during their pregnancy. The level of male involvement in ANC in Palabek Refugee Settlement was 39% (164/423). Male involvement in ANC was positively associated with access to information on ANC (AOR 3.0; 95%Cl: 1.7-5.4) and frequent couple discussion on ANC (AOR 10.1; 95%Cl: 5.6-18.0). However, it was negatively associated with distance ≥ 3 km to the health facility (AOR 0.6 ;95%Cl: 0.4-1.0). Conclusions Approximately one in three male partners in Palabek Refugee Settlement were involved in ANC. Male partners who had access to information during ANC and those who had frequent discussions were more likely to get involved in ANC. Men who lived ≥ 3 km from the health facility were less likely to be involved in ANC. We recommend intensified awareness creation on importance of male involvement in ANC and implementation of integrated community outreaches to reduce distance to the health facility.